Black Smoke : African Americans and the United States of barbecue - Miller, Adrian (Chapel Hill : The University of North Carolina Press, 2021)
"Across America, the pure love and popularity of barbecue cookery has gone through the roof. Prepared in one regional style or another, in the South and beyond, barbecue is one of the nation's most distinctive culinary arts. And people aren't just eating it; they're also reading books and articles and watching TV shows about it. But why is it, asks Adrian Miller--admitted 'cuehead and longtime certified barbecue judge--that in today's barbecue culture African Americans don't get much love? In Black Smoke, Miller chronicles how Black barbecuers, pitmasters, and restauranteurs helped develop this cornerstone of American foodways and how they are coming into their own today"--.
"A Ferris and Ferris book."
new book 2022 fall.
Includes bibliographical references (pages 267-292) and index.
Keywords: Barbecuing -- United States; African American cooking; African American cooks